Effect of zinc oxide nano-particles supplementation on the histoarchitecture of small intestine of broilers - DOGRA, SAMRITI; DEVI, JONALI; SARMA, KAMAL (The Indian Journal of Animal Sciences, 2023)
In this study, a total 240 Vencobb strain broiler chicks were randomly divided into 3 groups. The broilers fed with basal diet were kept as control group (C), while T1 and T2 groups broilers were fed with zinc oxide nanoparticles @45 mg/kg and @90 mg/kg of basal diet, respectively. Eight chicks out of each group were sacrificed at an interval of 14, 21, 28, 35 and 42 days and tissue samples from different parts of small intestine (duodenum, jejunum and ileum) from each bird were collected, processed, stained and studied for various micrometrical parameters. Histomorphometrical parameters of small intestines showed significantly increasing trend with the advancing age in control, T1 and T2 groups. Significantly higher histomorphometrical parameters of small intestines were recorded in zinc oxide nano-particle supplemented groups when compared to control. Zinc oxide nanoparticle supplementation @90 mg/kg diet in feed of broilers significantly improved histomorphometric characteristics, viz. villus height of duodenum, jejunum and ileum; villus width of ileum, width of muscularis laminae in duodenum and ileum and height of epithelial cells in all three segments of small intestine. Therefore, it is concluded that zinc oxide nanoparticle can be used as a diet supplement for increasing the overall performance in broiler chicks during their growth period, however, supplementation of zinc oxide nanoparticle @90 mg/kg gave better result in broilers for overall better performance.